Спектральная эффективность корректирующего кодирования - Розенвассер, Д. М. (ХНУРЕ, 2012)
This article discusses the possibility of increasing the spectral efficiency of optical fiber transmission systems using error-control coding. To solve this problem expression approximating the gain from using of the error-control coding was derived. Also, the dependence of the spectral efficiency of the transmission system on the degree of encoding, error-control code rate and modulating coefficient was derived. Found the optimum spectral efficiency by using of the error-control coding. It was assumed that at the initial transmission system (before conversion) amplitude shift keying or quadrature - amplitude modulation was used. Nonbinary Reed-Solomon error-control codes were used. Application of error-control coding together with the transition to spectrally efficient methods of modulation in most cases, improve spectral efficiency of transmission systems. It is shown that the use of long codes with low bit error probability (which is typical for fiber-optic transmission system) improves spectral efficiency of transmission systems in two - three times.
Keywords: спектральная эффективность; корректирующий код; квадратурная амплитудная модуляция; степень кодирования